Survey of nutrition-related KAP levels in children and adolescents with early-onset severe obesity in Qinhuangdao city - Wang, Miao; Han, Jinlin; Tian, Dawei; Liang, Zhi; Chen, Ning; Wu, Humeng (Journal of the Pakistan Medical Association, 2025)
Objective: To investigate the nutrition-related knowledge, attitude and practice levels of children and adolescents with early severe obesity, and to analyse the influencing factors. Method: The cross-sectional study was conducted from January 2022 to January 2023 in Qinhuangdao city, China, and comprised children and adolescents with early-onset severe obesity. Based on the median nutrition-related knowledge, attitude and practice level, the subjects were divided into a ‘high’ group A and ‘low’ group B. The baseline data of the two groups was compared, and the relevant factors affecting nutrition-related knowledge, attitude and practice levels were analysed. Data was analysed using SPSS 22. Results: Of the 250 subjects, 127(50.8%) were females, 123(49.2%) were males, 79(31.6%) were aged >14 years, 70(28%) 6-14 years, 69(27.6%) 2-6 years and 32(12.8%) were <2 years. There were 127(50.8%) subjects in group A and 123(49.2%) in group B. The overall mean knowledge, attitude and practice score was 12.52±2.38 (range: 6-19), with median score 13(IQR=4). Body shape assessment, parental obesity, and parents’ education level were the influencing factors of nutrition-related knowledge, attitude and practice levels (p<0.05). Conclusion: Children and adolescents with early-onset severe obesity in Qinhuangdao were found to have a medium level of nutrition-related knowledge, attitude and practice, and the level was influenced by body shape assessment, parental obesity and parental education level. Key Words: Severe obesity, Children. Adolescents, Knowledge, Attitude, Practice, Influencing factors.